Effect Of Government Spending And Investment On Economic Growth In South Sulawesi - Amina, Sitti (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the effect of government spending and investment on economic growth in South Sulawesi Province. Methodology: This research employs a quantitative approach using secondary data and multiple linear regression analysis to examine the relationship between government spending, investment, and economic growth. Results: The results indicate that government spending has a significant positive effect on economic growth, while investment does not show a statistically significant effect when analyzed individually. However, simultaneous analysis reveals that government spending and investment together significantly influence economic growth. Novelty: This study provides empirical evidence on the differing impacts of fiscal and investment variables on regional economic growth in an Indonesian provincial context. Findings: Well-managed government spending, particularly in strategic sectors, plays a more dominant role in stimulating economic growth compared to investment alone. Originality: The originality of this study lies in its focus on South Sulawesi Province using recent regional economic data to assess fiscal and investment effectiveness. Conclusions: Optimizing government spending allocation and improving the effectiveness of investment policies are essential to achieving sustainable economic growth in South Sulawesi. Type of Paper: Empirical Quantitative Research Paper.